Effect of implantation defects on the corrosion of 316L stainless steels in primary medium of pressurized water reactors. (June 2016) - Dumerval, Marie; Perrin, Stéphane; Marchetti, Loïc; Sennour, Mohamed; Jomard, François; Vaubaillon, Sylvain; Wouters, Yves
Highlights: Implanted samples of stainless steel were oxidized in primary water. Microstructure of oxide formed on these samples was studied. Oxide layer growth kinetics was obtained by ion beam techniques. Tracers experiments were performed in order to study hydrogen and oxygen diffusion. Abstract: 316L samples were implanted with xenon ions in order to generate defects (characterised as cavities) in the alloy subsurface region. Their oxidation kinetics in pressurized water reactor primary water at 325 °C were determined using ion beam analyses. After a 24 h exposure, the internal oxide layer reaches a thickness equivalent to the implanted affected depth (90 nm) which does not change much for longer exposure duration. Two-stages corrosion experiments followed by secondary ion mass spectrometry analyses have revealed two oxygen diffusion regimes in the internal oxide layer, which seems to be linked with the distribution of implanted defects.